Photocatalytic CO2 Conversion with H2O to CO and CH4 Over V2C/TiO2 Composite - Beenish Tahir; Mustafa Jawad Nuhma; Muhammad Tahir; Abdulrahman Alraeesi; Ali A. Jazie; Naveen Kumar (Journal of Engineering and Sustainable Development, 2025)
Photocatalytic reduction of CO2 to valuable chemicals and fuels requires highly efficient semiconductor materials, and most available photocatalysts are less efficient. Due to their unique electrical properties, the new family of two-dimensional materials known as MXenes has drawn much interest in photocatalytic applications. The vanadium carbide (V2C) is one of the significant MXenes being considered because of its many advantages over other materials. In this work, V2C-loaded TiO2 composites were synthesized and tested for photocatalytic reduction of CO2 with H2O to produce value-added CO and CH4 fuels in a continuous flow photoreactor system. The optimized 10 % V2C-TiO2 was responsible for CO and CH4 formation of 1233.8 and 85.2 µmol g-1 h-1, respectively, which were many-fold higher than using pure TiO2. This enhanced photoactivity of the composite was due to increased conductivity, many active sites, and higher light absorbance, which allowed for the efficient separation of charge carriers and light absorbance. Thus, MXenes, particularly 2D V2C MXene, would be a promising cocatalyst to combine with a semiconductor to maximize photocatalytic activity during CO2 reduction application.